The diagonals of parallelogram QRST and intersect at point U. If RS = 10, ST = 12, and RU = 9.5, find the length of

Answers

Answer 1
Answer: I am assuming that parallelogram QRST is  rectangle.
RS is the width and ST is the length. 
RT is the diagonal. RU is half of the diagonal and TU is the other half of the diagonal.

Length = 12 ; Width = 10

to find the diagonal: 
d = √(L²+W²
d = √ 12² + 100²
d = √ 144 + 100
d = √244
d = 15.62

RU + TU = 15.62
TU = 15.62 - 9.5
TU = 6.12

Related Questions

The length of a rectangle is 5 feet more than twice the width. The perimeter is 130 feet. Find the dimensions.
Which number is the largest?A) 1.81B) 1.08C) 1.801
The sum of two numbers is 47, and their difference is 15. What is the larger number?
What is the slope of the line 6x-2y=15?a) -7.5b) -3c) 2.5d) 3
Find the zeros of the function by rewriting in intercept form.Y=2X^2-4xy=2C^2-11X-21I need the answer and the work please.

In the figure above, lines k, l, and m intersect at a point. If x + y = u + w , which of the following must be true?

Answers

From the given equation we have x=z and t=z. Therefore, option B is the correct answer.

Given that, lines k, l, and m intersect at a point.

What is vertical angle theorem?

Vertical angles theorem or verticallyopposite angles theorem states that two opposite vertical angles formed when two lines intersect each other are always equal (congruent) to each other.

From the given figure,

Using vertical angle theorem, we have

x°=t°

y°=u°

w°=z°

If x + y = u + w, then

x+u=u+z

⇒ x=z

If x + y = u + w, then

t+u=u + z

⇒ t=z

So, x=z and t=z

From the given equation we have x=z and t=z. Therefore, option B is the correct answer.

To learn more about the vertical angle theorem visit:

brainly.com/question/8119520.

#SPJ2

Answer:

B)

Step-by-step explanation:

First, let's write down what we know based on the Vertical Angle Theorem and the info given by the question:

1. Vertical angle theorem claims that opposite angles are the same, therefore:

  • y=u
  • x=t
  • w=z

2. We know from the problem that:

  • x+y = u+w

3. Now for the proofing:

Since  x+y = u+w, let us try to cross off the variable u and see if we can get x equaling to w.

We know that y=u, so let us switch out y for another u, allowing the same variable to cross out

x+y = u+w --> x+u = u+w --> x=w

Ok now we know x=w, and recall that w=z. So x would also equal to z!

Let us try to proof z=t:

We know that x=t

But now we also know that x=z (from previous)

Therefore we can substitute the z in for x in x=t and voila z=t!

Try finding out if y=w. No matter how many equations you create, they are not the same. It would not make sense either if you use this equation: x+y = u+w. If w and x are the same then y cannot be anything except being equal to "u". We cannot prove that u is equal to anything else either.

Therefore the answer is B)

How do you answer these questions?

Answers

First page:

Angles B and C >>> vertical angles

C + D is 180 because they form a >>> straight line

D and E are congruent bc they are alternating interior.

Second page:

If A = 72 degrees, then D is 72 degrees. E and G would also be 72 degrees.

If A = 72, just remember that A + B = 180 (bc together they are a straight line), so 180-72 = 108. So Angle B is 108 degrees.

If B is 108 degrees, then C, F and H are also 108 degrees.

So the actual questions in the order listed:

B = 108 degrees

D = 72 degrees

E = 72 degrees

F = 108 degrees

H = 108 degrees

G = 72 degrees

Xz is 15 and the perimeter of triangle xwz is 50 what is the length of wz

Answers

Well if you have a congruent lines, and you have P = 50 and xz = 15 P = xz + 2 * wz so to find wz you need to subtract xz and divide by 2 50 - 15 = 35 and then divide by 2 to get 17.5

Simplify(5p^2-3)+ (2p^2-3p^3)

Answers

If you would like to simplify (5 * p^2 - 3) + (2 * p^2 - 3 * p^3), you can calculate this using the following steps:

(5 * p^2 - 3) + (2 * p^2 - 3 * p^3) = 5 * p^2 - 3 + 2 * p^2 - 3 * p^3 = - 3 * p^3 + 7 * p^2 - 3

The correct result would be - 3 * p^3 + 7 * p^2 - 3.
(5 x^(2) -3)+(2 x^(2) -3 x^(3))

Select the equivalent expression

Answers

to my calculations i think it’s c

Solve log(2x+3) = 3

Answers

log_a x=z  ⇔  a^z=x

In this case:
log (2x+3)=3  ⇔  10³=2x+3

we have the following equation:
10³=2x+3
1000=2x+3
2x=1000-3
2x=997
x=997/2
x=498.5

Answer:  x=498.5

Answer:

997/2

Step-by-step explanation: